Public policies for the institutionalization of knowledge networks in the IES in Mexico, since the end of 90s - de Sierra Neves, María Teresa (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2014)
In this paper we analyze public policies in science and technology that were applied in Mexico since the late twentieth century; the impact that they had on the promotion and development of the academic networks as new way of organization, management and knowledge sharing. Particularly, it is interested in the interaction between the changes caused by these policies, in the configuration of group networks and research centers, and the development of academic networks as a result of natural evolution of the scientific disciplinary and interdisciplinary activity. In the work are distinguished the following relevant dimensions: the internationalization of knowledge, as a result of the complexity of the knowledge; the context of new regulations in which they develop ways of organization of knowledge in universities; the historical context with new demands of society and government agencies. The methodological approach of the study is that of the new institutionalism, and the research strategy has been based on literature reviews and interviews with qualified operators. The main conclusion of the work is that the effect on the generation of knowledge networks for the implementation of these policies is not homogeneous. It is mediated by the institutional and historical conditions of each institution and disciplinary cultures.